Type species designations and other nomenclatural notes on Palaearctic Melolonthinae and Cetoniinae (Coleoptera: Scarabaeoidea: Scarabaeidae) - Smetana, Aleš; Smith, Andrew B.t. (Zootaxa, 2006)
The nomenclatural status and correct spelling of several genus-group and species-group names of Palaearctic scarab beetles are discussed. Type species are designated for the following genus-group names of Palaearctic Melolonthinae: Brachydema Fairmaire, 1881 (type species Brachydema lamberti Fairmaire, 1884), Microtrichia Brenske, 1900 (type species Phytalus eurystomus Burmeister, 1855), Pseudohoplia Reitter, 1890 (type species Hoplia gabriellina Fairmaire, 1887), and Sparophysa Burmeister, 1855 (type species Pachydema bullata Burmeister, 1855). Type species are designated for the following genus-group names of Palaearctic Cetoniinae: Melanosa Mulsant & Rey, 1871 (type species Cetonia morio Fabricius, 1781), Pachnotosia Reitter, 1891 (type species Cetonia marmorata Fabricius, 1792), Polydomia Thomson, 1880 (type species Macronota cervina Wallace, 1867), Potosia Mulsant & Rey, 1871 (type species Cetonia floricola Herbst, 1790), and Tetragonus Gory & Percheron, 1833 (type species Agestrata dehaani Gory & Percheron, 1833). The following genus-group names were determined to be unavailable: “Microtrogus” Mikšić, 1965, “Paramonotropus” Medvedev, 1951, “Sinoliocola” Alexis & Delpont, 1998. Clarifications are made on the nomenclature and correct spelling of several other genus-group and species-group names.